The historical beginnings of digital arts in the Kingdom of Saudi Arabia - Al-garni, Asma Ali Abdullah (Journal of Humanities & Social Sciences, 2020)
The aim of the research is to get to know digital art through a historical account of it, and to know the first beginnings of digital art in the Kingdom of Saudi Arabia through an art exhibition, to identify the artists and artists who turned to digital art in the Kingdom of Saudi Arabia, and the researcher followed the historical approach, and the research dealt with: the first beginnings Digital art in the Kingdom of Saudi Arabia in the first plastic art exhibition, and artists and artists of digital art in the Kingdom of Saudi Arabia, in addition to the reality and future of digital art in terms of (pros and cons), and the results of the research showed that the beginnings of digital art was in 1998 AD as the first plastic exhibition, and was the first Personal digital art exhibition in 2008 AD in an exhibition without appointment for the artist Dr. Manal Al-Ruwaished, and the first collective digital art exhibition in 2009 AD in an exhibition for the digital art group consisting of Manal Al-Ruwaished and artist Hana Al-Shibli and artist Hoda Al-Ruwais and Fawzih Al-Mutairi and Aisha Al-Harithi My digital calligraphy in 2010. Based on the results, the researcher recommended documenting the beginnings of digital art as the first formative exhibition in specialized references for digital art, and counting the digital artists and writing them in references specialized in digital art.